Development of an educational video to improve HIV-related knowledge, attitudes and prevention among company workers in Ecuador. (January 2015) - Cabezas, María del Carmen; Fornasini, Marco; Barmettler, David; Ortuño, Diego; Borja, Teresa; Albert, Adelin
Objective: To develop and assess an innovative educational video package for improving HIV knowledge, attitudes and practices among company workers in Ecuador. Methods: The design and development of the HIV prevention educational video was based on the results of a large-scale survey conducted in 115 companies (commerce, manufacturing and real estate) and among 1, 732 workers in the three most populous provinces of Ecuador (Pichincha, Guayas and Azuay). Two focus groups (workers of different job categories and HIV experts from various domains) evaluated the video by means of an 11-item questionnaire scoring the concept, script, technical aspects, potential impact, content and quality of the digital production. Results: The video produced was 16-minutes long. The two focus groups indicated their overall satisfaction with the initial version of the video and their scores were high. They felt the video kept their interest, was easy to understand, and evidenced the good use of graphics, voice audio and narrative to impact on the audience. The experts were, however, slightly more critical than workers and made some minor suggestions about the content and the need to test the video's cultural appropriateness and degree of comprehension, both of which improved the video prior to its final release. Conclusion: Video-based HIV intervention programmes targeting company workers may have value in improving knowledge and reducing the risk of HIV transmission in Ecuador.